Between the ecclesiastical authority and the local leadership: the parish priests of the diocese of Tucumán during the first Peronism (Quinto Sol, 2015)
The historiography on the relationship of the Catholic Church and Peronism in Argentina focused on the links between the high spheres of the ecclesiastical institution and the State from a political-institutional perspective. Based on the sociocultural approaches developed in recent years around the Church and Catholicism, this study seeks to broaden and make the approach to this topic more complex. To this end, we analyze the course of the parish priests of Famaillá and Monteros - towns located in the center of the sugar agro-industrial cordon of the province of Tucumán - between 1946 and 1952. Taking into account the changes introduced by the emergence of Peronism in the dynamics political and social of the sugar communities, the study asks about the role of parish priests, their forms of intervention in local populations and the implications of their political options in the parish sphere. In this way, we investigate the tensions that ran through both trajectories, crossed by the dilemma between obedience to the ecclesiastical hierarchy and the affirmation of a local leadership.
Keywords: Catholic Church; Peronism; politics